2021
DOI: 10.1002/rrq.401
|View full text |Cite
|
Sign up to set email alerts
|

Is the Science of Reading Just the Science of Reading English?

Abstract: The science of reading has made genuine progress in understanding reading and the teaching of reading, but is the science of reading just the science of reading English? Worldwide, a majority of students learn to read and write in non-European, nonalphabetic orthographies such as abjads (e.g., Arabic), abugidas/alphasyllabaries (e.g., Hindi), or morphosyllabaries (e.g., Chinese). Over a decade ago, I argued that the extreme inconsistency of English spelling-sound correspondence had confined the science of read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 124 publications
(134 reference statements)
1
30
0
Order By: Relevance
“…For the present study, we focused on articles in which English was the primary language of the participants, as consistency of orthography can moderate the RAN‐reading relationship (Araújo et al, 2015) and the largest number of published studies are in English. We acknowledge that English is not a representative orthography (Share, 2008; Share, 2021), but that this analysis serves as a starting point and allows specific conclusions to be drawn in at least this one language. As we were interested in early predictors of reading ability, we only included articles in which the initial timepoint with RAN assessment was in (the US equivalent of) kindergarten or preschool (the earliest stage at which RAN can be measured reliably) and reading was subsequently measured at some point in Grades 1–5.…”
Section: Methodsmentioning
confidence: 99%
“…For the present study, we focused on articles in which English was the primary language of the participants, as consistency of orthography can moderate the RAN‐reading relationship (Araújo et al, 2015) and the largest number of published studies are in English. We acknowledge that English is not a representative orthography (Share, 2008; Share, 2021), but that this analysis serves as a starting point and allows specific conclusions to be drawn in at least this one language. As we were interested in early predictors of reading ability, we only included articles in which the initial timepoint with RAN assessment was in (the US equivalent of) kindergarten or preschool (the earliest stage at which RAN can be measured reliably) and reading was subsequently measured at some point in Grades 1–5.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of evidence supporting the value of explicit GPD instruction comes from studies with English speakers (Castles, Rastle, & Nation, 2018; Ehri et al, 2001). Critics have suggested that because the English writing system is less transparent and much more complex than other writing systems, research in English may have limited relevance for a universal science of reading (Duncan et al, 2013; Share, 2008a, 2021; Ziegler & Goswami, 2006). Landerl (2000) hypothesized that in more transparent orthographies such as Portuguese, the orthographic structure itself may provide sufficient unequivocal information about the alphabetic writing system to activate students’ phonological decoding abilities without explicit instruction in grapheme–phoneme relations and phonics.…”
Section: Graphophonemic Approachmentioning
confidence: 99%
“…Last but not least, we need to consider the importance of generalising results across languages, orthographies, and scripts. Huettig and Ferreira argue, as have others before them (most recently Blasi et al, 2022;Share, 2021), that the focus of reading in English leads to models, theories, and reading instruction methods that are not generalisable to other languages. Figure 1 can be extended to a three-dimensional plot, where language and script characteristics would make up an additional dimension.…”
Section: A Response To "The Myth Of Normal Reading" By Huettig and Fe...mentioning
confidence: 92%